2000
DOI: 10.1097/00007890-200001150-00030
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Hypertension Associated With Pulmonary Occlusive Vasculopathy After Allogeneic Bone Marrow Transplantation

Abstract: High-dose preparative chemotherapy and radiation before transplantation are thought to have contributed to the development of vasculopathy in this patient, because arterial occlusion by intimal fibrosis and atypical veno-occlusion are often associated with lung injury due to chemoradiation. An open lung biopsy is essential for diagnosing pulmonary vascular disease presenting signs compatible with posttransplantation pulmonary hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(42 citation statements)
references
References 6 publications
2
39
0
1
Order By: Relevance
“…The interesting and speculative issue in this case is the underlying pathogenesis of the vascular damage. PAH as a complication of marrow transplantation has been reported rarely [4][5][6], and in each of these cases was attributed to intensive conditioning; none occurred in the context of GVHD. Vaksmann et al described the onset of PAH 5 months post-transplant in an 8-year-old girl conditioned with busulphan, cyclophosphamide, and cytarabine [4].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The interesting and speculative issue in this case is the underlying pathogenesis of the vascular damage. PAH as a complication of marrow transplantation has been reported rarely [4][5][6], and in each of these cases was attributed to intensive conditioning; none occurred in the context of GVHD. Vaksmann et al described the onset of PAH 5 months post-transplant in an 8-year-old girl conditioned with busulphan, cyclophosphamide, and cytarabine [4].…”
Section: Discussionmentioning
confidence: 99%
“…Vaksmann et al described the onset of PAH 5 months post-transplant in an 8-year-old girl conditioned with busulphan, cyclophosphamide, and cytarabine [4]. Seguchi et al reported PAH in the 3 rd month post-transplant in a heavily pretreated 20-year-old male conditioned with total body irradiation, cyclophosphamide, and cytarabine [5]. Open lung biopsy demonstrated partial to complete occlusion of small pulmonary arteries by fibrous proliferation of the intima, together with multiple veno-occlusive lesions in small pulmonary veins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Application of this frequency to the incidence rate of idiopathic PAH yields an estimated incidence rate of ''idiopathic'' PVOD of 0.1-0.2 cases per million [17,18]. However, PVOD can also occur in patients with associated diseases, including HIV infection [19][20][21], bone marrow transplant [22][23][24][25][26][27][28], connective tissue diseases [13,14,29], sarcoidosis [30] or pulmonary Langerhans cell granulomatosis [8,31,32], suggesting that PVOD could have a much higher prevalence than indicated by these registries.…”
Section: Epidemiology and Risk Factorsmentioning
confidence: 99%
“…However, pulmonary hypertension has been described in only a few case reports from the immediate post-treatment period. [11][12][13][14][15][16][17] Pulmonary hypertension is a progressive condition characterized by increased pulmonary artery pressure that may lead to right ventricular failure, which is associated with increased mortality without treatment. 18 Direct measurement of pulmonary artery pressure by right-heart catheterization is the gold standard for diagnosis of pulmonary hypertension.…”
Section: Introductionmentioning
confidence: 99%